OPTIMIZATION OF CONCENTRATION AND DURATION OF SEED NUTRIPRIMING WITH IRON SULPHATE FOR SEED QUALITY ENHANCEMENT IN BLACKGRAM - B. SAI SUDHA*, K .BAYYAPU REDDY, K. RADHIKA; V. SAIDA NAIK (The Journal of Research ANGRAU, 2021)
The investigation was carried out to optimize the concentration and duration of nutripriming withiron sulphate for seed quality enhancement in blackgram variety, Tulasi. The experiment was conducted during 2019-20 using Factorial Completely Randomized Design(FCRD) and replicated four times. Seeds were subjected to nutripriming with various concentrations (0, 0.01%, 0.05%, 0.1% and 0.5%) of iron sulphate for different durations (0, 2, 4, 6 and 8 h). Primed as well as unprimed seed of blackgram were tested for germination and seedling growth using between paper method. It is evidentthat nutripriming with iron sulphatewas effective in improving the seed quality of Tulasi.Among all the concentrations, 0.1% iron sulphate was found effective in recording highest germination (%), seedling length (cm) and seedling vigour index. Irrespective of concentration, priming for 6h showed maximum improvement for seed quality parameters. Nutripriming with 0.05% iron sulphate for 6 h resulted in better enhancement of germination and seedling quality parameters in blackgram.